2020
DOI: 10.1016/j.tmaid.2019.101500
|View full text |Cite
|
Sign up to set email alerts
|

Environmental investigation of respiratory pathogens during the Hajj 2016 and 2018

Abstract: A B S T R A C TBackground: Respiratory tract infections are common in the context of the Hajj pilgrimage and respiratory pathogens can be transmitted via contact with contaminated surfaces. We sampled surfaces during the Hajj to detect the presence of respiratory bacteria and viruses. Methods: Frequently touched surfaces at Mecca, Mina, Arafat and Medina were sampled. The common respiratory pathogens were tested by qPCR. Results: 70/142 (49.3%) environmental samples collected were positive for at least one res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This randomized trial, like other smaller trials [ 9 15 ], failed to provide conclusive evidence on facemask efficacy against laboratory-confirmed or clinical respiratory infections. Inconclusiveness of this and previous studies might be attributed in part to respiratory pathogens having multiple routes of transmission including contact with contaminated surface [ 26 , 27 ] and fecal-oral transmission of some respiratory viruses [ 28 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This randomized trial, like other smaller trials [ 9 15 ], failed to provide conclusive evidence on facemask efficacy against laboratory-confirmed or clinical respiratory infections. Inconclusiveness of this and previous studies might be attributed in part to respiratory pathogens having multiple routes of transmission including contact with contaminated surface [ 26 , 27 ] and fecal-oral transmission of some respiratory viruses [ 28 ].…”
Section: Discussionmentioning
confidence: 82%
“…Our cRCT, which was a field study in real time, was unable to refute our null hypothesis. Lack of facemask efficacy observed in this trial could be attributed to limited facemask use by participants (only 24.7% used daily and 47.7% used intermittently in the intervention group), the substantial proportion of participants in the control group who used facemasks, the inability to follow participants after Hajj or the likely contamination of masks [9,26]. Though more in the intervention group consistently wore masks for defined periods daily, facemask use by controls further reduced the ability of the study to detect differences in infection rates between the study arms.…”
Section: Plos Onementioning
confidence: 84%
“…Out of these, two studies evaluated the frequency of H-CoV contamination on airport surfaces and reported prevalences of 3.3% [ 70 ] and 7.5% [ 51 ]. One study investigating the frequency of contamination by respiratory pathogens of areas and surfaces in places associated with worship reported an overall HCoV prevalence of 1.4% [ 42 ], whereas in a university classroom, desktops and the doorknob were the surfaces most commonly contaminated with H-CoV [ 34 ]. The prevalence of SARS-CoV contamination was investigated in two studies on hospital surfaces, and both revealed the high frequency of SARS-CoV contamination on surfaces exposed to SARS-CoV positive patients [ 35 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hajj pilgrimage is one of the largest annual mass gatherings which usually takes in Saudi Arabia with over 2 million pilgrims characterized by a high prevalence of respiratory illness among pilgrims from Malaysia and other parts of the world (1)(2)(3). There is a continued rise in the prevalence of RTIs despite the preventive practices among the Hajj pilgrims (4,5). The COVID-19 pandemic that resulted in over 3,424,380 deaths with over 165 million people infected worldwide as at 11th August 2020 based on the figures from the Johns Hopkins University (6).…”
Section: Introductionmentioning
confidence: 99%